The Interface of International Marketing and Entrepreneurship Research : Review, Synthesis, and Future Directions - Yang, Man; Gabrielsson, Peter (SAGE Publications, 2018)
There is no intensive review available of research at the interface of international marketing and entrepreneurship. This article systematically logs and organizes the subject matter and provides research suggestions. An organizing framework with three main dimensions—international marketing, the nature of marketing, and entrepreneurship—guides the literature review, which relies on a full search of articles relevant to international marketing and entrepreneurship published in academic journals over the past two decades (1997–2016). The study adopts a qualitative research approach to analyze 169 articles that meet the definitions of both international marketing and entrepreneurship research. Nine research types emerge at the intersection of international marketing and entrepreneurship research, and the study examines the theoretical and empirical trends of each type. A promising avenue for future studies would be cross-cultural comparative research on the individual–opportunity nexus in marketing across countries. More mixed-method and longitudinal research designs are also welcomed. The authors conclude by offering suggestions for future interdisciplinary research.
Keywords: entrepreneurship; future research; international marketing; review; fi=Kansainvälinen liiketoiminta|en=International Business|